Prognostic role of p53 condon 72 polymorphism in north indian lung cancer patients treated with platinum based chemotherapy - Kumari, Ankita (My University, 2016)
p53 gene is located at chromosome 17p13.1. p53 protein plays an important role in maintaining genomic stability by undergoing cellular arrest during DNA damage. Depending on the extent of DNA damage it either performs DNA repair or cellular apoptosis. Objectives: To investigate the association of p53Arg72Pro with susceptibility and improved survival status in lung cancer patients. Results: lung cancer patients with mutant (CC) genotype found to have significant association with overall survival (HR=0.65; 95% CI=0.45-.0.95; p=0.03) and on adjustment made with Cox regression model for different parameters association was nearly significant (HR=0.68; 95% CI=0.63-1.16; p=0.06). Female lung cancer patients with any (GG, GC (HR=0.08; 95% CI=0.02; p=0.0005) and CC (HR=0.21; 95% CI=0.06-0.67; p=0.0085)) genotype showed significant improve in overall survival showing p53Arg72Pro genotype. Conclusion: The present study found no significant association of p53Arg72Pro genotype and other epidemiological and clinic-pathological parameters towards increased susceptibility and pathological development of lung cancer in different provinces of North Indian population. However nearly significant association was found for overall survival of lung cancer patients with mutant (CC) genotype. Females lung cancer patients with any (GG, GC and CC) genotype showed significant improve in overall survival showing p53Arg72Pro genotype to be the independent prognostic factor for females in North Indian population.
Keywords: polymorphism; p53; lung cancer